The role of ‘living laboratories’ in accelerating the energy system decarbonization - Zhong Fan; Jun Cao; Taskin Jamal; Chris Fogwill; Cephas Samende; Zoe Robinson; Fiona Polack; Mark Ormerod; Sharon George; Adam Peacock; David Healey (Energy Reports, 2022)
To decarbonize the energy system by the year 2050, it is crucial that innovations are trialled in a ‘real world’ setting for the purpose of increasing public adoption and support, and for providing insights to decision-makers to ensure their decisions are effective and influential. Together, renewable energy systems, distributed and digitized ‘smart’ energy networks (SEN) provide opportunities to maximize energy efficiency, reduce transmission losses and drive down greenhouse gas emissions. Yet, such integrated Smart Local Energy Systems (SLES) are in the early stages of development and the technologies that underpin them lack testbeds where they can be developed and tested in a real-world environment. Here we demonstrate the potential role of one of Europe’s largest ‘at scale’ multi-vector Smart Energy Network Demonstrator—SEND, developed within a ‘living laboratory’ setting that provides the ‘blueprint’ for the development and testing of low-carbon energy technologies on the UK’s journey to net zero. Based on the SEND platform and data, we have developed and demonstrated several novel AI based smart algorithms for intelligent SLES control and management. We are also working with industry partners to develop a digital twin of the smart energy system on our campus.